Ответ:
x=
; y= ![\frac{9}{22} \frac{9}{22}](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7B22%7D)
Пошаговое объяснение:
3x + xi - 2y - 8yi = -3 - 4i
3x - 2y + xi - 8yi = -3 - 4i
3x - 2y + i(x - 8y) = -3 - 4i
Два комплексных числа равны, если их действительные части равны, и их мнимые части равны.
![\left \{ {{3x-2y= - 3} \atop {x-8y = - 4}} \right. \left \{ {{3x-2y= - 3} \atop {x-8y = - 4}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7B3x-2y%3D%20-%203%7D%20%5Catop%20%7Bx-8y%20%3D%20-%204%7D%7D%20%5Cright.)
умножте на -3
![\left \{ {{3x-2y = - 3} \atop {-3x + 24y -12}} \right. \left \{ {{3x-2y = - 3} \atop {-3x + 24y -12}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7B3x-2y%20%3D%20-%203%7D%20%5Catop%20%7B-3x%20%2B%2024y%20-12%7D%7D%20%5Cright.)
22y = 9
y= ![\frac{9}{22} \frac{9}{22}](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7B22%7D)
3x - 2(
)= -3
x= ![-\frac{8}{11} -\frac{8}{11}](https://tex.z-dn.net/?f=-%5Cfrac%7B8%7D%7B11%7D)